Making a meal for a Dragon - Owen, Ruth, 1967- (Minneapolis, Minnesota : Bearport Publishing Company, 2022)
"What do you feed a fire-breathing friend that finds its way to your place for dinner? A marvelous meal fit for your dragon guest (that you'll love, too)! Start with an appetizer of crunchy claw crackers and a sweet-and-spicy ginger drink. For the main course, serve up a pepperoni pie shaped just like your dragon friend-complete with colorful scaly skin. Then, finish the meal with sweet fire-colored meringues. While you're at it, don't forget to brush up on dragon myths so you'll have plenty to talk about during your mythical meal"--
Includes bibliographical references and index.
Ages 10
Grades 2-3
Keywords: Cooking -- Juvenile literature; Cookbooks